DIRECTIONS, FORMS AND SECTORS OF MODERNIZATION OF AGRICULTURAL ENTERPRISES - Matkovskyi , P.Ye. (The actual problems of regional economy development, 2018)
The concept of the article is oriented on the substantiation of the components of the modernization system of agroformations. Considerable attention is paid to the directions, forms, spheres of manifestation and implementation of agricultural enterprises. Among the forms of modernization are defined: social, technological, institutional, personnel, etc. In the course of the study, methods of comparison, analysis, dialectics were used. it is determined that the state should become the initiator and organizer of the modernization of the country's economy and its agrarian sector, in particular, in the context of the economic crisis, because modernization is one of the few methods of achieving a healthy competitive struggle in the arena of a modern global market.